Pengaruh Lingkungan Kerja Dan Kepuasan Kerja terhadap Kinerja Pegawai Kantor Camat Dompu - Nurul Fitria Yulita,; Thatok Asmony,; Djoko Suprayetno, (Manajemen Kreatif Jurnal, 2023)
This study aims to determine the effect of the work environment , job satisfaction on performance at the Dompu sub-district office. The type of research used is associative research in the form of causation with a quantitative approach. The population and respondents in the study were 43 employees. The data collection method used is the census method. Data collection tool is a questionnaire. The analytical tool used is Multiple Linear Regression analysis using SPSS versions 25 and 26. The results of the data analysis show that (1) the work environment has a positive and significant effect on the performance of the Dompu sub-district office. (2) job satisfaction has a positive and significant effect on the performance of the Dompu sub-district office.